Physical Properties and Effect in a Battery of Safety Pharmacology Models for Three Structurally Distinct Enteric Polymers Employed as Spray-dried Dispersion Carriers - Ryan M Fryer; Mita Patel; Xiaomei Zhang; Katja S Baum-Kroker; Akalushi Muthukumarana; Brian Linehan; Yin-Chao Tseng (Frontiers Media S.A., 2016)
Establishing a wide therapeutic index (TI) for pre-clinical safety is important during lead optimization (LO) in research, prior to clinical development, although is often limited by a molecules physiochemical characteristics. Recent advances in the application of the innovative vibrating mesh spray-drying technology to prepare amorphous solid dispersions may offer an opportunity to achieve high plasma concentrations of poorly soluble NCEs to enable testing and establishment of a wide TI in safety pharmacology studies. While some of the amorphous solid dispersion carriers are generally recognized as safe for clinical use, whether they are sufficiently benign to enable in vivo pharmacology studies has not been sufficiently demonstrated. Thus, the physical properties, and effect in a battery of in vivo safety pharmacology models, were assessed in three classes of polymers employed as spray-dried dispersion carriers. The polymers (HPMC-AS, Eudragit, PVAP) displayed low affinity with acetone/methanol, suitable for solvent-based spray drying. The water sorption of the polymers was moderate, and the degree of hysteresis of HPMC-AS was smaller than Eudragit and PVAP indicating the intermolecular interaction of water-cellulose molecules is weaker than water-acrylate or water-polyvinyl molecules. The polymer particles were well-suspended without aggregation with a mean particle size less than 3 µm in an aqueous vehicle. When tested in conscious Wistar Han rats in safety pharmacology models (n=6-8/dose/polymer) investigating effects on CNS, gastrointestinal, and cardiovascular function, no liabilities were identified at any dose tested (30-300 mg/kg PO, suspension). In brief, the polymers had no effect in a modified Irwin test that included observational and evoked endpoints related to stereotypies, excitation, sedation, pain/anesthesia, autonomic balance, reflexes, and others. No effect of the polymers on gastric emptying or intestinal transit was observed when measured using a barium sulfate tracer material. Finally, in telemetry-instrumented rats the polymers had no effect on acute or 24-hr mean blood pressure and heart rate values at doses up to 300 mg/kg. Thus, the properties of the three enteric polymers are appropriate as spray-dried dispersion carriers and were benign in a battery of safety pharmacology studies, demonstrating their applicability to enable in vivo safety pharmacology profiling of poorly soluble molecules during LO.